The Influence of Halal Certification, Halal Awareness, and Brand Image on Interest in Buying Halal Food Products: An Empirical Study of Consumers in Indonesia - Djakasaputra, Arifin; Juliana; Aditi, Bunga; Fachrurazi; Mas’ad, Muhammad Aunurrochim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to determine the effect of variables on halal certification, halal awareness, brand image, and intention to buy halal food products. This research is a study of consumers of halal products. The data in this study were obtained by distributing online questionnaires to respondents who were consumers of halal products in Indonesia. The quantitative approach uses surveys as primary data and data analysis using structural equation modelling (SEM). Respondents in this study were consumers of halal products, with a total of 480 respondents who were consumers of halal food products. The method used in the sampling of respondents was purposive sampling with the criteria of having bought halal food. Collecting data by using research instruments, data analysis is quantitative. The data analysis method used in this study uses descriptive analysis to identify characteristics and the Structural Equation Modeling (SEM) analysis method with SmartPLS 3.2.6 software. The analysis in the SEM model can be divided into two stages, namely, the measurement model and the structural analysis model. The results showed that halal certification has a positive effect on purchase intention. Halal certification has a positive effect on brand image. Brand image has a positive effect on purchase intention. Halal awareness has a positive effect on purchase intention. Halal certification positively and significantly affects purchase intention through brand image.